Resource-Use Efficiency in Small-Holder Broiler Production in Oshimili North Local Government Area, Delta State - Ukwuaba , S.I.; Inoni, O.E. (International Journal of Poultry Science, 2012)
Resource-use efficiency among small-holder broiler farmers in Oshimili North Local Government Area of Delta State was examined. Primary data collected with structured questionnaire from randomly selected 100 respondents, were analyzed using appropriate statistics. The result revealed that small-holder broiler farming was profitable in the study area. Feed cost was dominant consisting of about 35.05% of total cost and about 37.70% of total variable cost of production. Labour and day-old chicks had inverse relationship with broiler output while medication though not significant and quantity of feed had positive influence on broiler output. Efficiency estimates showed that farmers in the area were generally inefficient in the use of resources while the most significant constraint facing these farmers was inadequate finance with a mean score of 2.60. In order to increase output and profitability as well as promote efficient utilization of resources in broiler production, government should as a matter of policy address the intractable problem of lack of access to farm credit by small-holder farmers, provide guaranteed funds at affordable interest rate and capture the significant factors affecting broiler production.